The acquisition of Italian morphosyntax and its interfaces in different modes of acquisition - Belletti, Adriana (Language acquisition & language disorders ;, 2015)
A major contribution to the study of language acquisition and language development inspired by theoretical linguistics has been made by research on the acquisition of Italian syntax. This book offers an updated overview of results from theory-driven experimental and corpus-based research on the acquisition of Italian in different modes (monolingual, early and late L2, SLI, etc.), as well as exploring possible developments for future research. The book focuses on experimental studies which address research questions generated by linguistic theory, providing a detailed illustration of the fruitf.